Methionine one-electron oxidation: Coherent contributions from radiolysis, IRMPD spectroscopy, DFT calculations and electrochemistry. (November 2016) - Scuderi, Debora; Bergès, Jacqueline; de Oliveira, Pedro; Houée-Levin, Chantal
Abstract: Methionine is an essential amino acid, unfortunately prone to oxidation. The mechanism of its oxidation by OH radicals has been studied for more than 40 years and still remains misunderstood. We have reinvestigated the oxidation of this residue in model peptides, aiming at i) improving the identification of free radicals by the use of more modern quantum chemistry methods; ii) reinvestigating the one-electron reduction potentials as a function of the position in the sequence; iii) identifying the final compounds, which were still unknown; iv) reinvestigating the intramolecular electron transfer (IET) involving this residue. Highlights: Methionine oxidation has been reinvestigated by time-resolved, electrochemistry and mass spectrometry methods. The final compounds have been identified. Methionine oxidation can be repaired by intramolecular electron transfer in peptides.